Integrated Coastal Zone Management 2009
DOI: 10.1002/9781444316285.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Fishing Vessels Affected by a Marine Protected Area – The Case of Small‐Scale Trawlers and the Marine Protected Area in Nha Trang Bay, Vietnam

Abstract: Are Marine Protected Areas positive for adjacent fisheries? This is a study of the technical efficiency of small-scale trawlers in Nha Trang, Vietnam following establishment of Nha Trang Bay Marine Protected Area (NTB-MPA) that imposed a trawl ban to protect marine biodiversity and regenerate fish stocks. Data were collected through a survey of small-scale trawler owners. Using a stochastic frontier analysis, this study demonstrates that engine power, household size and operating characteristics of vessels str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…1B ). Fishing is prohibited at this site, but occurs in other sections of Ninh Van Bay and adjacent waters ( Ngoc, Flaaten & Anh, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…1B ). Fishing is prohibited at this site, but occurs in other sections of Ninh Van Bay and adjacent waters ( Ngoc, Flaaten & Anh, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…gillnet versus trawl fisheries) (Andersen 2002;Greenville et al 2006). Some studies have used engine power to represent boat capital (Duy and Flaaten 2016;Greenville et al 2006;Kompas et al 2004a;Oliveira et al 2016) while others have used boat size, often hull length or in some cases a combination of length and width representing the total "deck area" (Fousekis and Klonaris 2003;Ngoc et al 2009;Pascoe et al 2017b;Squires and Kirkley 1999). Other studies have also used volumetric measures, such as gross registered tonnage (GRT) (Jeon et al 2006;Squires et al 2003;Susilowati et al 2005;Viswanathan et al 2001), or the amount of fishing gear deployed (Duy and Flaaten 2016;Fousekis and Klonaris 2003;Kompas et al 2004a;Lokina 2009;Rust et al 2017).…”
Section: Efficiency Analysis In the Fishing Industrymentioning
confidence: 99%
“…Common measures of fishing effort range from hours fished to just the presence/absence of fishing on a particular day (e.g. Duy and Flaaten 2016; Jamnia et al 2015;Kirkley et al 1995;Ngoc et al 2009). Crew size has been used as a variable input in a number of studies (Kirkley et al 1995;Kirkley et al 1998;Ngoc et al 2009;Van Nguyen et al 2019), but this variable is often highly correlated with boat size as bigger boats have more crew members employed.…”
Section: Efficiency Analysis In the Fishing Industrymentioning
confidence: 99%
“…The influence of the exchange rate on RSHM was examined by (Heard et al, 2012), stating that the exchange rate affected RSHM. (Ngoc et al, 2009) in the period of 1986-2006 when the liberalization of the forex market economy was implemented, showed that changes in currency exchange rates negatively affected the profitability of banking companies. (Royle and Laing, 2014) in his research showed that changes in currency exchange rates did not have a significant positive effect on ROA profitability.…”
Section: The Influence Of Kurs On Rshmmentioning
confidence: 99%